Analysis of the 2008 Olympic Greco-Roman wrestling competition - Curby, D.; Dziedzic, S.; Fraser, S. (2008)
This report summarizes some of the findings from an analysis of the scoring characteristics of the Greco-Roman wrestling at the Beijing Olympic Games. Greco-Roman wrestling has been a part of the modern Olympic Games since their inception in 1896. International competition is overseen by the International Federation of Associated Wrestling Styles (FILA). 166 National Federations belong to FILA. Greco-Roman wrestling is one of the two main forms of international wrestling and does not allow for holds to be taken below the waist. According to the ranking of the last World Cup of Greco-Roman wrestling, the leading countries in this style are: Russia, Hungary, Iran, Georgia, Korea and the United States. Other top wrestling nations include Cuba, Sweden, Ukraine, Azerbaijan, Armenia and Egypt. Countries must qualify their athletes for Olympic competition and the 139 allotted spots in 7 weight classes. Nineteen countries won medals in Beijing.